Penerapan Media Audio-Visual Untuk Mengembangkan Keterampilan Berbahasa Inggris Kelas V MI Islamiyah Suwawal 02 - Sanaya Rahma Fitria; Manunal Ahna; Ahmad Saefudin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research discusses the application of audio-visual media to improve English language skills at the elementary school level. This research is motivated by the low ability of students to listen and speak English, so it is appropriate to improve it with the help of audio-visual media. In compiling this article, the researcher used a qualitative descriptive research method. The subject of this study was an English teacher at MI Islamiyyah Suwawal 02. This study aimed to understand what the research subject experienced in the application of audio-visual media to class V MI, starting from the benefits of using audio-visual media during learning, the obstacles experienced in the application of audio-visual media, as well as student learning outcomes when learning to use audio-visual media. The results of the interviews show that with the application of audio-visual learning media, students are increasingly interested in participating in learning English, as well as providing better learning outcomes than before. The conclusion obtained from this study is that the Audio-Visual learning model can improve student learning outcomes.